НА ШЛЯХУ ДО НАЦІОНАЛЬНОГО ПОРОЗУМІННЯ: ЕВОЛЮЦІЯ ЕТНОНАЦІОНАЛЬНОЇ КОНЦЕПЦІЇ ОУН ПІД ВПЛИВОМ ДІЯЛЬНОСТІ НА ПІВДНІ УКРАЇНИ (Zaporizhzhia Historical Review, 2021)
The article is devoted to the problem of evolution of ethno-national conception of Organization of Ukrainian Nationalists during 1940th. An author traces the terms of development of nationalistic motion southward and their influence Ukraine on the liberation movement on the whole. By investigation of activity on South of Ukraine for nationalists there was complete departure from the doctrines of anti-semitism and national intolerance.